Outcomes post Ozaki procedure among children with aortic valve disease at Jakaya Kikwete Cardiac Institute, Dar es Salaam, Tanzania: a retrospective descriptive study - Zawadi Edward Kalezi; Alphonce Nsabi Simbila; Stella Mongella; Deogratias Nkya; Godwin Sharau; Felix Shonyela; Vivienne Mlawi; Naizihijwa Majani (BMC Cardiovascular Disorders, 2024)
Abstract Background Aortic valve reconstruction using glutaraldehyde-treated autologous pericardium, also called Ozaki procedure, is a surgical procedure for patients with aortic valve disease. Gratifying results have been reported in adult patients, however, limited published data is available in paediatric population. This study looked at clinical characteristics and early outcomes of children who underwent Ozaki procedure at our Institute. Methods This was a retrospective descriptive study conducted on children who underwent aortic valve reconstruction at Jakaya Kikwete Cardiac Institute (JKCI) from January 2019 through December 2022. Medical records of these children were reviewed to extract data on demographics, clinical characteristics, redo surgical interventions and survival. Results A total of 10 children underwent Ozaki procedure during the study period. Eight children had severe aortic regurgitation while 2 had severe aortic stenosis preoperatively. All children had either none or trivial aortic regurgitation immediately after surgery. None of them had redone operations throughout the follow-up period. There was no in-hospital mortality, however, one child died one-year after surgery. The mean follow-up period was 1.6 years with the longest follow-up time of 4 years. Conclusion Ozaki procedure showed encouraging early results among children with aortic valve disease who underwent surgical repair by this technique. Future studies with larger sample sizes and longer follow up periods to evaluate long-term results in this population are recommended.